Seignorage pooling of EMU, pool bias and seignorage change by the Euro - Nikolaus K. A. Läufer (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2003)
To deal with changes of capitalized seignorage due to EMU, we supply the still missing capital-theoretical framework. We show that seignorage pooling of EMU is composed of two components, a dynamic component and a static component. By its dynamic component, the pool provides insurance against seignorage losses from changes of national shares in European seignorage, while the static component is reflecting a problematic pool-bias. The seignorage model is then applied to simulate EMU-changes of capitalized seignorage in two scenarios for Germany. Estimates of changes in the literature are examined: Finally, recent (Dec. 6, 2001) decisions by the ECB with regard to seignorage-pooling are evaluated.
Keywords: E59; F33; F36; 330; European Monetary Union (EMU); Euro; seignorage; seignorage pooling; seignorage change; pool bias